I Felt that the World Belonged to Me”: The Significance of Civic Engagement among Palestinian University Graduates in Israel: Civic Engagement of Palestinian Graduates - Goldner, Limor (Advances in Social Sciences Research Journal, 2019)
The current study identified factors that characterize the significance of civic engagement in 24 Palestinian university graduates in Israel who were involved in extra-curricular civic-engagement programs as students. Using an interpretative phenomenological analysis of semi-structured interviews conducted five to 10 years after completing their higher education, three themes emerged. The first is related to the expansion of the graduates’ identity primarily as regards acquiring new skills and self-knowledge as well as greater self-competence. The second theme covers civic engagement as a vehicle for developing a political identity and social awareness. The third theme depicts activism as providing relief, especially from their studies. The findings are discussed within the framework of identity exploration.